Effectiveness of the Pro Tools Software to Enhance Vocal Music Students Singing Performance of a Polytechnic Institution in Middle of China - Hu, Juan; Phongsatha, Thanawan; Achwarin , Naree (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
The purposes of this research were to 1) determine the effectiveness of the integration of ProTools software as a supplementary tool enhancing vocal music students’ singing performance, and 2) to identify the students’ satisfaction toward using ProTools software. A mixed-method research design of the quasi-experiment and the interview were conducted. The participants were 80 vocal music students aged 18-20 years at a Polytechnic Institution in Middle of China. Forty samples were assigned into the control group, and the other 40 were the experimental group. The 10 students from the experimental group were selected for the interview. The control group was taught traditionally while the experimental group was taught using ProTools software. The independent sample T-test was applied for hypotheses testing, while the content analysis was used for qualitative data analysis. The results revealed that the students from the experimental group had higher scores than the control group in all skills—pitch, rhythm, enunciation, singing ability, performance ability, and emotion controlling. Therefore, ProTools software serves as an effective learning tool to improve student vocal music performance. In addition, the students showed a positive satisfaction towards using ProTools software as the blended learning to enhance singing performance